Pengembangan Game RC Car Simulator Menggunakan Augmented Reality - Herdianto Tri Setyaji; Wibisono Sukmo Wardhono; Issa Arwani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Implementation of Augmented Reality in game development has a great impact on user experience (UX). In development game with the simulation genre by implementating of marker-based Augmeted Reality is the main goal of this study. A game with Radio Control Car (RC) Simulator's theme has an description simulate the games as on the real world. The main target of this game itself is to produce a new user experience by increasing user experience and interaction with RC Car Simulator games without the presence of physical objects directly and without thinking of a large place to play it. In this study the selection of frameworks using the MDA framework as an appropriate concept in the development of RC Car Simulator games. In this game development is done by using a paper prototyping and followed by digital prototyping until all the elements of development that fit to the digital games. Play testing process that has been completed in this study is obtained from the use of Augmented Reality can be achieved with the existence of virtual objects displayed in the real world can provide user experience on aspects of usability testing, where almost 80% agree with what is expected by the developer where the results are satisfactory and a lot of feedback is obtained during the testing.